Crystal structure and NMR study of a bisperoxovanadium complex [NH4][VO(O2)2(ima)]. Issue 17 (2nd September 2017) - Zhang, Shaowei; Xia, Wen; Yang, Yueyue; Yu, Xianyong; Li, Xiaofang
Abstract: A novel bisperoxovanadium complex, [NH4 ][VO(O2 )2 (ima)] (1 ) (ima = imidazole-4-carboxamide), was synthesized by the reaction of NH4 VO3 and ima in the presence of H2 O2, and the structure was characterized by single-crystal X-ray technology. The adjacent [NH4 ][VO(O2 )2 (ima)] monomers further constructed a 3-D supramolecular framework through intra- and intermolecular hydrogen bonding interactions. The composition of the title complex solution was explored using a combination of multinuclear ( 1 H, 13 C and 51 V) magnetic resonance, heteronuclear single quantum coherence (HSQC), and variable temperature NMR in a 0.15 mol L −1 NaCl/D2 O solution that mimics physiological conditions. According to NMR experimental results, a pair of isomers (Isomers A andB ) are observed in aqueous solution, which are attributed to different types of coordination modes between the metal center and the ligands;Isomer B (the main product) has the same coordination structure as the crystal structure of [NH4 ][VO(O2 )2 (ima)]. The 51 V NMR experiment together with single-crystal X-ray diffraction results indicated thatIsomer A is the hexa-coordinated peroxovanadium species whileIsomer B is the hepta-coordinated species. Abstract :